Produccion de tomate de cascara (Physalis ixocarpa Brot) basado en laminas de riego y acolchado plastico - Lopez Lopez, R.=700 1 Arteaga Ramirez, R.; Vazquez Peña, M.A.; Lopez Cruz, I.L.; Sanchez Cohen, I.
(ES, En)
Ilus., 14 ref.
Keywords: PHYSALIS IXOCARPA; RIEGO; USO DEL AGUA; PRODUCCION; PRODUCTIVIDAD; TOMATE; MEXICO; TOMATE DE CASCARA; ECUACION DE PENMAN-MONTEITH; REVISTA CHAPINGO: SERIE HORTICULTURA